AFTERMATH OF THE NAIRA REDESIGN ON SMALL AND MEDIUM ENTERPRISES (SMEs) IN NIGERIA. (Journal of the Management Sciences, 2023)
This paper examines the aftermath of the Naira redesign on small and medium enterprises (SMEs) in Nigeria.  As a developing country, cash is the main mode of payment thereby making the economy cash based. The idea to redesign the Naira was hatched in the year 2022 by the Central Bank of Nigeria (CBN) with the approval of the then President. The policy was birthed to enable the CBN to control the Naira in circulation, manage inflation, combat counterfeiting, and bring to a halt the stockpiling of the Naira by corrupt persons amongst others. The policy was a good one with the intended capacity to address the issues it was meant to address. But evidence abounds that, its poorly execution amongst other factors is not in alignment with Nigeria's business operational realities, and consequently put a clog on the ease of doing business in Nigeria, low manufacturing capacity utilization, increased unemployment, increased inflation, increased debt and charging of high premium by banks and POS operators. It was therefore recommended that government and CBN should come up with policies and reforms that should ensure cash availability at various cash dispensing outlets to make trading activities easier, and equally lessen physical and economic hardship in carrying out their day-to-day economic activities.
Keywords: Naira Redesign; Small and Medium Enterprises; Nigeria